The Relevance of Zainudin MZ's Political Preaching Thoughts to Urban Community Development - Mastori, Mastori; Paimun, Paimun; Anim, Sarbini (Al-madinah: Journal of Islamic Civilization, 2024)
In practice, Islamic preaching in this era is more often displayed and preached only on the narrow aspects of spirituality and morality. Meanwhile, aspects of culture, social, economy, let alone politics are rarely mentioned. The involvement of preachers in politics is still considered taboo. In such conditions, Zainudin MZ emerged to break the taboo. With a brave attitude, the kyai not only preached politically verbally but also directly entered into the practice of democratic politics that was full of deceit. By using a qualitative descriptive method that uses research data in the form of books, journals, and videos related to Zainudin MZ's political thoughts and movements, several findings were produced: first, the relationship between preaching and politics for Zainudin MZ is an integralistic relationship that is reflected in his preaching material on the ethics of political preaching and criticisms of government policies. Second, Zainudin MZ's political activities are based on a strong spirit of Islamism. It was proven when mass organizations and political parties were prohibited from using Islamic principles with the implementation of the sole principle of Pancasila, Zainudin immediately left the world of practical politics and focused on preaching. For him, there was no point in being in a party if the principle was not Islamic. When the sole principle was revoked, he returned to being active in politics and even became the general chairman of the Islamic party. Third, Zainudin's involvement in practical politics found a new phenomenon that preaching politics is difficult to realize in the realm of democratic politics. Therefore, after feeling that his preaching idealism could not be implemented practically, Zainudin MZ chose to withdraw from politics and called his involvement in past politics the era of ignorance. Fourth, the substance of Zainudin MZ's preaching is very relevant for urban society, especially in maintaining Muslim identity and in facing various social, cultural and political challenges.